DAMPAK PENGGUNAAN APLIKASI ONLINE DICTIONARY PADA PEMBELAJARAN BAHASA INGGRIS DI MA AL-HIDAYAH MUARA TELANG - Ratmini Ratmini; Dahlia Dahlia (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The purpose of the reseach is to find students’ perceptions in using Online Dictionary in learning English. This study uses qualitative studies using those that aim to find the impact using Online Dictionary. The object of this research is the students of MA Alhidayah Muara Telang. The author takes 30 students of grade X science using the online dictionary as a sample. The method used by the author is the questionnaire. There are two impacts in this study, namely positive and negative impacts, the positive impact is that students easily understand the reading text, motivating students to be active in English. While the negative impact is the weak internet connection and the lack of funds in fulfilling the Quota.